Preparation of WC/Co composite powders by electroless plating. Issue 5 (1st April 2017) - Guo, L.; Xiao, L.R.; Zhao, X.J.; Song, Y.F.; Cai, Z.Y.; Wang, H.J.; Liu, C.B.
Abstract: Ultra-fine WC/Co composite powders were prepared by electroless plating in this study. The Co layers with an average thickness of 50–100 nm were uniformly and completely covered on raw WC particles with a diameter of 0.3–0.5 µm. The influences of electroless plating conditions on the composites were investigated. The Co layer covering on WC particles was controlled by the content of CoSO4 ·7H2 O, pH value and bath temperature. With increasing the content of CoSO4 ·7H2 O up to 25 g/L, both the weight gain and the plating rate markedly increased. However, when the content of CoSO4 ·7H2 O further increased to 30 g/L, while the weight gain displayed a slight decrease, the plating rate continued to increase moderately. Moreover, with the increase of pH value from 9.5 to 11, both the weight gain and the reaction time decreased. Furthermore, the plating rate exhibited an exponential relationship with the bath temperature. When the pH value, bath temperature and the concentration of CoSO4 ·7H2 O are 10, 80 °C and 25 g/L respectively, the weight gain of Co-coated WC composite powders is 185.1 mg/g.